Examination of Covid-19 Outbreak Dynamics, and Identification of Better Vaccine and Viral Drug Targets Through Genomic Analyses of Sars-Cov - Sezgin, Efe; Gürbüz, Bahar Anıl (01. Izmir Institute of Technology, 2022)
Since the emergence of the SARS-CoV-2 virus, which causes the COVID-19 disease, it continues despite the application of many vaccines and drug treatments. It has continuously mutated, therefore the effect of vaccines and drug treatments has begun to decrease and a permanent solution has not been found. The main hypothesis of thesis is that the conserved regions in the SARS-CoV-2 genome can be potential targets for new vaccines and drugs to eradicate the Covid-19 pandemic. In this study, a total of 807 sequences of the first emerging clades (L, O, S) of the SARS-CoV-2 human virus and its variants in the category of Variants of Concern (Alpha, Beta, Gamma, and Delta) were taken from different dates, and population genetic statistical tests were conducted. Human specific SARS-CoV-2 sequence analyses showed that the evolution of all viral proteins are primarily driven by negative selection. Interspecies tests using the RaTG13 Bat coronavirus, which has the most similar genome to the SARS-CoV-2 virus genome, showed that there was no fixed amino acid change divergence between the bat and human virus sequences for Membrane, Nsp8, Nsp10, and Nsp16, indicating high conservation. Then, a list of the amino acid changes among the SARS-CoV-2 human clades and variants was prepared for Membrane, Nsp8, Nsp10, and Nsp16. Since the regions outside of these changes are the most conserved, the functions of the Membrane, Nsp8, Nsp10, and Nsp16 and and interactions with other viral proteins should be investigated as potential targets for new vaccines and drug treatments.

COVİD-19 hastalığına neden olan SARS-CoV-2 virüsü ortaya çıkmasından bu yana üzerinden birçok aşı ve ilaç tedavisi uygulanmasına rağmen devam etmektedir. Süreç içerisinde sürekli olarak mutasyona uğramış bu nedenle bulunan aşı ve ilaç tedavilerinin etkisi azalmaya başlamıştır ve hala bu virüse karşı kalıcı bir çözüm bulunamamıştır. Ana hipotezimiz, SARS-CoV-2 genomundaki korunmuş bölgelerin COVİD-19 pandemisini ortadan kaldırmak amacıyla geliştirilen aşı ve ilaç stratejileri için potansiyel hedefler olduğudur. Bu çalışmada, SARS-CoV-2 insan virüsünün ilk ortaya çıkan kladları (L, O, S) ve endişe verici varyant kategorisinde yer alan (Alfa, Beta, Gama ve Delta) varyantlarının farklı tarihlerden toplam 807 adet sekansı alınmış ve popülasyon genetik istatistiksel testleri uygulanmıştır. Uygulanan tür içi testler sonucunda genom proteinlerinde negatif seçilimin hakim olduğu görülmüştür. SARS-CoV-2 virüs genomuna en benzer genoma sahip olan RaTG13 yarasa koronavirüsü kullanılarak yapılan türler arası istatistiksel analizler sonucunda ise; Membrane, Nsp8, Nsp10 ve Nsp16 proteinlerinde amino asit değişimine yol açan değişimler bakımından sabitlenmiş ayrışma olmadığı görülmüştür. Ardından Membrane, Nsp8, Nsp10 ve Nsp16 proteinlerinin SARS-CoV-2 insan virüsünün kladları ve varyantları arasında amino asit değişimine yol açan değişimlerinin listesi çıkarılmış ve bu değişimlerin dışında kalan bölgelerin en korunmuş bölgeler olmasından dolayı Membrane, Nsp8, Nsp10 ve Nsp16 proteinlerin fonksiyonları ve diğer proteinlerle etkileşimleri de araştırılarak potansiyel hedefler olabileceği ve bu bilgilere göre yeni aşı ve ilaç tedavileri ortaya konulabileceği belirtilmiştir.
Sars-cov-2'nin Genomik Analizleri Yoluyla Covıd-19 Salgın Dinamiklerinin İncelenmesi ve Daha İyi Aşı ve Viral İlaç Hedeflerinin Belirlenmesi
Thesis (Master)--Izmir Institute of Technology, Biotechnology, Izmir, 2022
Includes bibliographical references (leaves. 55-71)
Text in English; Abstract: Turkish and English
Keywords: COVID-19; SARS CoV-2; Genome analysis; Variants of concern